A Short-Term Efficacy of Anlotinib in the Treatment of Refractory Nasopharyngeal Inverted Papilloma: A Case Report - Yang, Pan; Meng, Gang; Shu, Qiuxia; Dong, Yan; Li, Chong; Lu, Yujiao; Li, Jianjun (Frontiers in Oncology, 2021)
To our knowledge, no studies have reported the use of anlotinib in the treatment of locally cancerous nasopharyngeal inverted papillomas that cannot be operated on or treated with radiotherapy. Here, we report a case of a 53-year-old woman diagnosed with recurrent local canceration of nasopharynx papilloma. Magnetic resonance imaging (MRI) showed that the right parapharyngeal space, nasopharynx, and ethmoid sinus were changed, and recurrence was considered. There was no indication for surgery or radiotherapy. Imaging showed that the tumor had obvious enhancement and abundant blood vessels. Immunohistochemistry showed that vascular endothelial growth factor receptor (VEGFR) 2 expression was positive in papilloma tissue and in local canceration tissue of the papilloma. After the patient’s consent was obtained, anlotinib treatment was started in May and ended in November 2019. Then, the patient was treated with intensity-modulated radiotherapy (IMRT) with planning gross tumor volume (PGTV) 66 Gy, planning clinical tumor volume 1 (PCTV1) 60 Gy, and planning clinical tumor volume 2 (PCTV2) 54 Gy in 33 fractions. No disease recurrence was reported at 4 months after radiotherapy.